2007
DOI: 10.1007/s12034-007-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective absorption of water from different oil-water emulsions with Psy-cl-poly(AAm) synthesized using irradiation copolymerization method

Abstract: The present paper deals with the functionalization of psyllium with acrylamide under the influence of gamma radiation using hexamethylene tetramine as a crosslinker. The polymer synthesized was characterized using FTIR spectroscopy, scanning electron microscopy and thermogravimetric analysis. The superabsorbent was then used further for the selective absorption of water from different oil-water emulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…These thermograms indicated that the first characteristic endothermic peaks for the exchangers are due to the loss of free water observed at ~80-83 o C for sample (I) and ~92.5 o C and 280 o C which may due to the removal of the water of crystallization for sample (II). The second exothermic peaks at ~ 245 and 447.5 o C for sample (I) and ~ 469.5 -649.7 o C for sample (II) may be due to complete decomposition of the organic part of the materials (13)(14)(15) and the third endothermic peaks at ~ 663 o C may be attributed the formation of metal oxide. It was found that, the weight losses are continued up to 650 o C, and no weight loss occurred in the range ~ 650-1000 o C. The trends are almost similar to those reported for zirconium phosphate (16) .…”
Section: Results and Discusionmentioning
confidence: 93%
“…These thermograms indicated that the first characteristic endothermic peaks for the exchangers are due to the loss of free water observed at ~80-83 o C for sample (I) and ~92.5 o C and 280 o C which may due to the removal of the water of crystallization for sample (II). The second exothermic peaks at ~ 245 and 447.5 o C for sample (I) and ~ 469.5 -649.7 o C for sample (II) may be due to complete decomposition of the organic part of the materials (13)(14)(15) and the third endothermic peaks at ~ 663 o C may be attributed the formation of metal oxide. It was found that, the weight losses are continued up to 650 o C, and no weight loss occurred in the range ~ 650-1000 o C. The trends are almost similar to those reported for zirconium phosphate (16) .…”
Section: Results and Discusionmentioning
confidence: 93%
“…This can be explained on the basis of * OH concentration, which is initially sufficient enough to propagate the polymerization reaction till optimum concentration is reached and further increase in the amount of solvent resulted in termination of polymerization due to excessive increase in * OH concentration (Fig 1b, eq.13) [19]. As exhibited by Fig 2a, P g increased with the increase in time and reached up to maximum value (132.5%) at 180 min and decreased afterwards with time.…”
Section: Optimization Of Different Reaction Parametersmentioning
confidence: 99%
“…As exhibited by Fig 2a, P g increased with the increase in time and reached up to maximum value (132.5%) at 180 min and decreased afterwards with time. This could be due to the fact that with increase in reaction time the active sites on the backbone and monomer increases, leading to increase in grafting but once the optimum is reached, the concentration of free radicals limits the length of polymeric chain by initiating numerous chains simultaneously which results in decreased P g [19]. (162.4%).…”
Section: Optimization Of Different Reaction Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…by the synthetic conditions, such as the n AAm /n MBAA in polymeric networks and by the nature of swelling media. These types of hydrogels containing functional groups have a potential to be used as colon specific drug delivery devices and can be used for water absorption from oil-water emulsions [24][25][26]. In this communication, meso-2,3-dimercaptosuccinic acid-Ce(IV) redox couple was used to synthesize the crosslinked copolymer of acrylamide and N,N′-methylene bis(acrylamide) in acidic aqueous medium.…”
Section: Introductionmentioning
confidence: 99%